Potencial turístico para el desarrollo del turismo rural comunitario en la ciudad de Marcabal - provincia de Sánchez Carrión – 2019 - Vera Oloya, Hammer Jonathan (2019)
The present research work was carried out taking as a scenario the District of Marcabal, Province of Sánchez Carrión, whose objective was to determine the tourist potential of the area with the purpose of developing the community rural tourism, as an alternative parallel to the work carried out by the communities Belonging to this district, the research carried out is descriptive, not experimental, the Inductive-Deductive Method, Hypothetical-Deductive Method was used, data collection and the survey were used as a research technique, to validate the reliability of the data obtained, the Cronbach Alpha method was applied, obtaining 0.802 for the data collection instrument of the tourism potential variable and 0.775 for the community rural tourism variable; The population was made up of the inhabitants of the Marcabal district who are of working age, a representative simple was obtained through the statistical method of 147 inhabitants, to whom the data collection instrument was applied, and with the information obtained, was able to meet the objectives of the thesis, test the research hypothesis, and propose strategies to develop rural community tourism, obtaining as a main result that the study variables are positively related, with a Pearson correlation coefficient equal to 0.79, and as a result of the correlational analysis of the variables, it was concluded that the tourism potential of the Marcabal district positively influences the development of rural community tourism.